Dyslipidemia and the Prevalence of Hypertension: A Cross-Sectional Study Based on Chinese Adults Without Type 2 Diabetes Mellitus - Wenke Cheng; Jingqi Zhuang; Siwei Chen (Frontiers in Cardiovascular Medicine, 2022)
BackgroundIn clinical practice, it is frequently observed that patients with hypertension often coexist with dyslipidemia. However, studies on atherosclerotic indices and the prevalence of hypertension are still limited. The purpose of this study was to assess the relationship between atherosclerotic indices and the prevalence of hypertension in Chinese adults without type 2 diabetes mellitus.MethodsIn this paper, a cross-sectional study was conducted based on 117,056 adults in 11 Chinese cities (Shanghai, Beijing, Wuhan, Suzhou, Shenzhen, Changzhou, Nantong, Guangzhou, Hefei, Nanjing, and Chengdu) from 2010 to 2016. Besides, the raw data was obtained from the public database (www.Datadryad.org), while eight atherosclerosis indices namely the atherogenic coefficient (AC), Castelli's risk index I (CRI-I) and II (CRI-II), the atherogenic index of plasma (AIP), the cholesterol index, the lipoprotein combined index (LCI), non-high-density lipoprotein cholesterol (non-HDL-C) and triglycerides/high-density lipoprotein cholesterol (TG/HDL-C) were analyzed in this study. Apart from that, two groups of continuous variables were measured using the Mann-Whitney test, and categorical variables were analyzed using the Chi-square test. Differences between multiple groups of continuous variables were investigated using Kruskal-Wallis one-way analysis of variance (ANOVA) and Dunn's test. Furthermore, Spearman correlation analysis and multivariate logistic regression analyses were performed to assess the relationship between atherosclerotic indices and blood pressure levels, and the prevalence of hypertension, respectively. The results of multivariate logistic regression analyses were expressed as the odds ratio (OR) and their corresponding 95% confidence intervals (CIs). Moreover, the receiver operating characteristic (ROC) curve was depicted to further analyze the predictive value of the atherosclerotic indices on the prevalence of hypertension.ResultsThe atherosclerosis indices were higher in the hypertensive population compared to those in the normotensive population. Meanwhile, systolic blood pressure (SBP) and diastolic blood pressure (DBP) were linearly and positively correlated with atherosclerotic indices. In addition, multivariate logistic regression analysis showed that the cholesterol index and non-HDL-C were observed to be positively associated with the prevalence of hypertension (p for trend < 0.05). Moreover, the prevalence of hypertension increased by 3.7% (OR: 1.037; 95% CI: 1.009-1.065; p = 0.009) and 6.1% (OR: 1.06; 95% CI: 1.033–1.091; p < 0.001), respectively, as per 1-standard deviation (SD) increase in the cholesterol index and non-HDL-C. Beyond that, ROC analysis demonstrated that the cholesterol index and non-HDL-C have a good predictive value for the prevalence of hypertension in women, with under the ROC curve (AUC) of 0.659 and 0.684 and cut-off values of 47.94 and 134.34 mg/dl, accordingly.ConclusionsIn Chinese adults without type 2 diabetes mellitus, atherosclerotic indices were significantly higher in hypertensive populations compared with those in normotensive populations, regardless of hypertension levels. Meanwhile, SBP and DBP were linearly and positively related to atherosclerotic indices. Besides, the cholesterol index and non-HDL-C were independent risk factors for the prevalence of hypertension, and they could be adopted for effectively predicting the prevalence of hypertension in women.